2000
DOI: 10.1007/s002590050540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radiotherapeutic response in non-small cell lung cancer patients by technetium-99m MIBT and thallium-201 chloride SPET

Abstract: The purpose of this study was to investigate the relationship between technetium-99m hexakis-2-methoxyisobutylisonitrile (99mTc-MIBI) accumulation in tumours and response to radiotherapy in non-small cell lung cancer patients in comparison with the findings obtained using thallium-201 chloride (201Tl). Simultaneous dual single-photon emission tomography (SPET) imaging with 600 MBq 99mTc-MIBI and 111 MBq 201Tl was performed in 31 patients with biopsy- or sputum cytology-proven lung cancer. SPET images were acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Previous reports concerning pre-therapeutic scintigraphic prediction of tumour response to treatment have suggested that poor responders will exhibit less intense accumulation of 99m Tc-MIBI than good responders [8,9,10,11,12,13,14,15,16]. Given these observations, we hypothesized that hypoxic conditions would interfere with the accumulation of 99m Tc-MIBI in tumour cells.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous reports concerning pre-therapeutic scintigraphic prediction of tumour response to treatment have suggested that poor responders will exhibit less intense accumulation of 99m Tc-MIBI than good responders [8,9,10,11,12,13,14,15,16]. Given these observations, we hypothesized that hypoxic conditions would interfere with the accumulation of 99m Tc-MIBI in tumour cells.…”
Section: Discussionmentioning
confidence: 93%
“…Subsequently, one of the 99m Tc compounds was introduced to the medium at 2×10 6 cells/370 kBq/ml after achieving equilibrium of oxygen tension measured with O 2 microelectrodes (MT Giken, Tokyo, Japan). 201 Tl chloride (Nihon Medi-physics, Nishinomiya, Japan) was simultaneously added as a comparison at 185 kBq/ml because this tracer is often used in the diagnosis of various malignant lesions [1,5,6,11,13,14]. Total incubation volume was 5 ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Furthermore, it has been shown that Tc-99m methoxy isobutyl isonitrile (MIBI) SPECT faithfully identifies not only the mediastinal lymph node metastases in patients with NSCLCs, 15 but also the chemotherapy response in both small-cell lung carcinoma (SCLC) 16 and NSCLCs. 17 The functional imaging mode of SPECT has a capability to visualize and measure molecular processes in vivo. However, it suffers from low spatial resolution, in comparison with CT or MRI.…”
mentioning
confidence: 99%